RARE EARTH ELEMENT ANOMALIES IN CRANDALLITE GROUP MINERALS FROM THE SCHUGORSK BAUXITE DEPOSIT, TIMAN, RUSSIA - Mordberg L.E.; Stanley C.J.; Germann K. (My University, 2000)
Crandallite group minerals from the Devonian bauxite deposit of Schugorsk, Timan, Russia, were studied by electron microprobe. Special attention was given to the distribution of the rare earth elements (REE). Of the A-site cations, essential are (oxides in wt.%) Ca (0.2 - 7.9), Sr (0.4 - 5.9), Ba (0.1 - 5.1), Pb (0.01 - 8.4), Y (to 2.4) and REE (to 21.6). Bi (A-site), Ga (B-site) and V (X-site) occur in trace amounts. Two main types of REE distribution in crandallite group minerals are distinguished. The first shows a clear negative Ce anomaly and partially depleted Pr; crandallite group minerals of this type formed under strong oxidising conditions (positive Eh and neutral to slightly alkaline pH values) and lost Ce due to its oxidation to Ce4+ and accumulation in other minerals such as anatase. The second type displays a positive Sm anomaly and a negative Pr anomaly. Individual crandallite group crystals belonging to this type, 1 - 40 μm in size, show a clear compositional zoning: the core is enriched in Ca, while the rim is enriched in S, Sr, Pb and the REE. This crandallite formed under reducing conditions related to stripping of Fe from the weathering profile. The presence of Sm2+ in the crandallite lattice is proposed, and the role of organic material in its reduction is discussed. A Pr anomaly was inherited from the parent rock. A comparison of REE distribution in crandallite group minerals from different weathering profiles suggests that these minerals can be used to distinguish conditions of weathering.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская